INNOVATIONS IN SOCIAL AND ENVIRONMENTAL REPORTING BASED ON THE KNOWLEDGE OF STAKEHOLDERS’ INFORMATION NEEDS - CARAIANI Chirata; DASCALU Cornelia; LUNGU Camelia Iuliana; GUSE Gina Raluca (Annals of the University of Oradea: Economic Science, 2009)
Starting form the accounting status as a social and institutional practice and the economic role of financial reporting, the paper addresses the issue of social and environmental accounting and reporting regulation. We propose an analysis of the main rep